Dynamics of occupational mobility: an empirical analysis based on headhunting data. Issue 2 (3rd April 2017) - Feng, Shilan; Tan, Ya; Gong, Liutang
Abstract: This paper analyses occupational mobility in the labour market using survey data from a headhunting company. Four aspects of occupational mobility are discussed: the frequency of occupational mobility, cross-industry mobility, cross-ownership mobility and the influence of the macro economy on occupational mobility. The following are our findings: (1) educational level may insignificantly or negatively influence occupational mobility; (2) the younger generation is more active in the labour market; (3) although the public sector provides stable job opportunities, labour mobility in the first five years is not lower in the public sector than in the private sector; and (4) Party members are more frequently occupationally mobile.